2021
DOI: 10.1103/physrevlett.126.246602
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Engineering inRMn6Sn6(R=

Abstract: Exploration of the topological quantum materials with electron correlation is at the frontier of physics, as the strong interaction may give rise to new topological phases and transitions. Here we report that a family of kagome magnets RMn 6 Sn 6 manifest the quantum transport properties analogical to those in the quantum-limit Chern magnet TbMn 6 Sn 6 . The topological transport in the family, including quantum oscillations with nontrivial Berry phase and large anomalous Hall effect arising from Berry curvatu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(40 citation statements)
references
References 41 publications
3
37
0
Order By: Relevance
“…Thus, materials containing kagome lattices are an exciting platform to explore the quantum level interplay between geometry, correlation, and topology. For instance, certain kagome magnets are found to exhibit electronic nematicity, giant spin-orbit tunability, and topological Chern quantum phases [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Kagome superconductors with competing orders have been identified for over 40 y [17][18][19], such as LaRu 3 Si 2 with T C of 7 K and a fundamental kagome band structure [20].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, materials containing kagome lattices are an exciting platform to explore the quantum level interplay between geometry, correlation, and topology. For instance, certain kagome magnets are found to exhibit electronic nematicity, giant spin-orbit tunability, and topological Chern quantum phases [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Kagome superconductors with competing orders have been identified for over 40 y [17][18][19], such as LaRu 3 Si 2 with T C of 7 K and a fundamental kagome band structure [20].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic exchange interaction splits the spin-up and spin-down Dirac cones, while the combination of out-of-plane magnetization and Kane-Mele type spin-orbit coupling further opens the Chern gap for the spin-polarized Dirac fermions. Though the spectroscopic and some preliminary electric transport data have been reported 16,17 , the quantum transport behavior of this kagome Chern magnet remains largely unveiled, which questions the key topological transport features of Chern-gapped Dirac fermions. Here we use the combination of electric, thermoelectric and thermal transport to characterize this quantum magnet and to discover its topological charge-entropy scaling.…”
mentioning
confidence: 94%
“…The former provides the source of topological nontrivial band structure, while the latter can drive magnetic instabilities. In this regard, several transition metal based kagome magnets are of current interest, which exhibit many-body interplays and Chern quantum phases [8][9][10][11][12][13][14][15][16][17][18] . Among these kagome magnets, TbMn 6 Sn 6 stands out owing to its pristine kagome lattice (without other atoms in the kagome lattice plane) and strong outof-plane magnetization (persisting to above room temperature).…”
mentioning
confidence: 99%
“…For TbMn 6 Sn 6 , a SOC-induced gap opens at the Dirac point, mainly consisting of in-plane Mn orbitals, at 0.2 eV above the Fermi level has been found in density functional theory (DFT) calculations [1]. Experimentally, Ma and coworkers [5] systematically investigated the topological transport in the RMn 6 Sn 6 family and found that the effective Chern gap and the Dirac cone energy decrease from R = Gd to Er. However, how electronic structures evolve with R elements and temperatures through spin reorientation is not well understood.…”
Section: Introductionmentioning
confidence: 94%
“…The rare-earth Tb atoms, possessing a strong easy-axis magnetocrystalline anisotropy (MA), * liqinke@ameslab.gov antiferromagnetically couple with the Mn atoms and align the Mn spins along the out-of-plane direction below the spin-reorientation temperatures T SR . This discovery of quantum-limit Chern topological magnetism in TbMn 6 Sn 6 has rekindled the interest in the RMn 6 Sn 6 family of compounds, where different R atoms and correspondingly a variety of magnetic structures provide a rich platform to explore quantum phenomena [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%